Employee Performance: Compensation and Career Development - Johannes Jonni Hendra Sagala; Ivan Gumilar Sambas Putra (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the effect of compensation and career development on employee performance at Pos Indonesia (Persero) Bandung. The method used is descriptive and verification method with a population of 40 people and samples taken for this study, while the analytical method used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS) Ver.23.00. The sampling technique used in this research is probability sampling technique with simple random sampling technique. The results showed that there was an effect of compensation, career development on employee performance at PT Pos Indonesia (Persero) Bandung.